Pengaruh Literasi Keuangan Terhadap Minat Menabung Mahasiswa Fakultas Ekonomi Dan Bisnis Islam UIN STS Jambi Di BANK Syariah - Rahmah Tulwaidah; Novi Mubyarto; Muhammad Ismail (JURNAL RISET MANAJEMEN (JURMA), 2023)
Financial education is an activity that aims to increase knowledge and skills in financial management. The 2019 Indonesian National Financial Survey shows the level of Islamic financial literacy is only 8.93 percent, meaning that only nine out of a hundred Indonesian adults are familiar with Islamic financial products. The 2019 National Financial Literacy and Inclusion Survey (SNLIK) found a financial literacy rate of 38.03% and a financial inclusion rate of 76.19%. This is because the Indonesian people in general do not have a good understanding of the characteristics of different financial products and services. Therefore, this study examines how financial literacy affects the interests of students of the Faculty of Economics and Islamic Economics, UIN STS Jambi. in Islamic banks. The purpose of this study was to measure the impact of financial literacy on savings in students of the Faculty of Islamic Economics at UIN STS Jambi Islamic bank. This research uses quantitative methods. Data collection tools in this study were observation and questionnaires/cursors. Primary data and secondary data are used as data sources. The informants of this study were students of the Faculty of Economics and Islamic Economics, UIN STS Jambi. From the research results it is known that the financial literacy variable has a significant effect on student savings